Landslide susceptibility assessment along Biyara-Tawella road, Kurdistan region, NE-Iraq - Mohammed, Fahmy Osman; Ahmed, Ashna Jalal; Mohammed, Sarkhel Hawre (Sulaimani Journal for Pure and Applied Sciences, 2020)
Landslide hazard assessment is carried out for the slope failures along the 12km road-cut between Biyara-Tawella which is considered a crucial road connecting the Iraq-Kurdistan region with the Iranian border; in the meantime, it is an important tourist route during the summer and spring season. Slope stability assessments consist of twenty-four stations were done include a regional survey of slopes and a detailed discontinuity assessment was performed along the outcropped rock units represented by the highly deformed Qulqula Formation, quaternary clastic deposit, and some local body of pillow basalt. Different types of failures in the area were identified and classified along the cut slopes, from most to least abundant are rockfall, wedge siding, and lateral detachments theses unstable slope contain many joint sets which is acted as lateral, back or composite back release surfaces during slope failure. The earthquake effect as a trigging mechanism of rockfalls leads to decreasing stability along the roadsides. Different rock physical factors have been used and evaluated; the highly fractured properties of rocks, intense rainfall, and freeze-thaw cycles consider the main factors influencing the slope failure. The slopes were assessed by using landslide possibility index (LPI), it shows various geo-hazard categories that range between "moderate hazard" to "very high" LPI categories and “low” to “high” hazard categories. Kinematic analysis carried out for two sites only by using DIPS V6.008 and the results show wedge sliding at site No.22 and lateral detachment in site No.23. Rockfall hazard assessment system (RHRS) developed by the Oregon State Highway Division has drawn based on vehicle vulnerability and elements regarding the rockfall hazard. The analysis of twenty-four cross-section of the cut slopes shows various unacceptable risk categories and it needs remedial works.
Keywords: Hazard rating; Kinematic analysis; Landslide possibility index; slope failure